Multimodal therapy with or without irreversible electroporation for unresectable locally advanced pancreatic adenocarcinoma: a systematic review and meta-analysis. Issue 5 (May 2022) - Sugumar, Kavin; Hurtado, Alex; Naik, Ilora; Hue, Jonathan J.; Rothermel, Luke D.; Ammori, John B.; Hardacre, Jeffrey M.; Winter, Jordan M.; Ocuin, Lee M.
Abstract: Background: Irreversible electroporation (IRE) is used as a locoregional treatment modality for patients with locally advanced pancreatic cancer (LAPC), but is non-curative and is associated with postoperative morbidity and mortality. We performed a systematic review and meta-analysis comparing survival outcomes of multimodal therapy with or without IRE. Methods: Separate searches were performed for multimodal therapy + IRE and multimodal therapy alone given the lack of comparative literature using PubMed, SCOPUS, and Cochrane Library in 3/2021. We determined overall survival (OS) and progression-free survival (PFS) from diagnosis and time of IRE. Treatment-related morbidity and mortality was determined. Results: Of 585 published articles, 48 met inclusion criteria for IRE (n = 27) and without IRE (n = 21) with data for 1420 (IRE) and 1348 (without IRE) patients. The 6/12/24 months OS with IRE was 99%/84%/28%. The 6/12/24 months OS without IRE was 99%/80%/12%. At 12 months from IRE, OS was 55% and PFS was 12%. The mean major complication and 90-day mortality rates for IRE were 17.95% and 2.65%. Conclusion: Multimodal therapy alone is associated with similar OS to multimodal therapy + IRE in patients with LAPC. Most patients progress and nearly half die within 1 year of the IRE procedure. Given the lack of quality prospective data, IRE should remain experimental and be used with caution in LAPC.